Ancaman Pidana Terhadap Pelaku Eksploitasi Seksual Anak Oleh Penyidik (Studi Kasus di Polresta Pulau Ambon dan Pulau-Pulau Lease) - Lixanya Felany Thenu; Juanrico Alfaromona Sumarezs Titahelu; Denny Latumaerissa (TATOHI: Jurnal Ilmu Hukum, 2021)
Introduction: Children in terms of national and state life are the future of the nation and the next generation of the ideals of the nation who have the right to survival, growth and development, participation, protection from acts of violence and discrimination. Purposes of the Research: This writing aims to examine and analyze the basis of investigators when giving criminal threats in the Minutes of Examination to perpetrators of child sexual exploitation and to analyze criminal threats against perpetrators of child sexual exploitation in accordance with the provisions of the legislation.Methods of the Research: The research method in this paper uses a normative juridical research type. The research approach used is the approach to legislation and the case approach. The procedure for collecting legal materials using library research, as well as legal materials analysis techniques is qualitative.Results of the Research: The basis for investigators in giving criminal threats to perpetrators of child sexual exploitation is the Law of the Republic of Indonesia No. 21 of 2007 concerning the Eradication of the Crime of Trafficking in Persons and Law no. 35 of 2014 concerning Child Protection because it was proven guilty of committing a criminal act of sexual exploitation of children. Criminal threats against perpetrators of child sexual exploitation in accordance with the provisions of the legislation, namely the Child Protection Act and the Criminal Act of Trafficking in Persons due to special minimum criminal sanctions in accordance with the provisions of positive law.